Influence of Side-Polished Fiber Surface Topography on Surface Plasmon Resonance Wavelengths and the Full Width at Half-Maximum - Zhiyong Bai; Mingquan Li; Jing Zhao; Shaoqing Cao; Ying Wang; Changrui Liao; Yiping Wang (IEEE Photonics Journal)
The influence of surface topography of side-polished fiber on resonance wavelengths and the full-width-at-half-maximum (FWHM) of surface plasmon resonance was evaluated in this work, based on the power spectrum density, wavelet, and finite-difference time-domain methods. The abrasive size determined the surface topography with various spatial period components. Coarse abrasives induced obvious low-frequency waviness features and a blue shift in the resonance wavelength. Fine abrasives introduced middle frequency microwaviness (0.5–1.0 μ m), which led to a blue or red shift, depending on the special period extent between 0.5 and 0.75 μ m. All waviness components broadened the FWHM because of the superimposed effect and the introduction of a high-order coupling model. High-frequency roughness components were able to shift the resonance peaks toward shorter wavelengths. Larger coupling energy tended to decrease the FWH, while high-order coupled modes tended to broaden the FWHM. We established a roughness model with Maxwell–Garnett theory incorporated into fractal dimensions. Experimental results demonstrated the feasibility of such a model. Small abrasive particles were able to narrow the FWHM, which is beneficial for identification of resonance wavelengths and evaluation of the surface plasmon resonance effect.